The Factors That Influence Organizational Citizenship Behaviour For The Environment - Huda, M. Nur; Nawangsari, Lenny C.; Sutawidjaya, Ahmad H. (International Review of Management and Marketing, 2021)
Employee voluntary behavior related to environmental awareness in the workplace is very important to support the sustainability of the organization. The purpose of this study was to determine the influence of leadership, organizational culture and job satisfaction on Organizational Citizenship Behavior for the Environment (OCBE) in 3 groups of employees in financial institutions (Banking, Pension Fund and Insurance). This type of research is a quantitative survey method. The study population was employees of financial institutions in Jakarta with a sample size of 126 people. In the 3 financial institutions studied, it can be proven that: 1. Leadership has no effect on OCBE and Work Satisfaction, 2. Organizational Culture affects OCBE and Work Satisfaction, 3. Work Satisfaction has an effect on OCBE, 4. Leadership has no effect on OCBE through Work Satisfaction and 5. Organizational Culture influences OCBE through Work Satisfaction. For further research, it is expected to further analyze other variables that affect OCBE for financial sustainability. Keywords: OCBE, Work Satisfaction, Leadership, Organizational Culture JEL Classifications: L2, J2 DOI: https://doi.org/10.32479/irmm.10779